Analisis Kinerja Pendapatan Daerah Kabupaten Garut - Safari, Cepi Triana (Department of Public Administration, 2019)
The implementation of regional autonomy and decentralization has implications for the broadening of regional authorities to regulate and manage regional revenues. The purpose of this study was to determine the performance of regional revenue in Garut Regency?s statement of budget realization since 2013-2017 fiscal years. The theory that I use in this study is the theory of Mahmudi (2016) which states that to analyze the performance of regional revenue can be done by analyzing the variance (difference) revenue budget, analysis of revenue growth, and financial ratio analysis. The method used in this research is descriptive method with a qualitative approach. The results showed that the regional revenue performance of Garut Regency in the 2013-2017 fiscal years based on the analysis of variance (difference) of the revenue budget was considered to be poor and then based on revenue growth was considered quite good. The regional revenue performance of Garut Regency 2013-2017 fiscal years based on the degree of decentralization ratio is considered less, based on the regional financial dependency ratio is still considered very high, and based on regional financial independence ratios was considered very low and included in the pattern of instructive relations.